Health impact of environmental and industrial noise - a narrative review - Stanovská, Markéta; Tomášková, Hana; Šlachtová, Hana; Potužníková, Dana; Argalášová, L'ubica (Medycyna pracy, 2024)
Industrial noise sources are among the environmental noise sources that are ranked second among the causes of ill health in Europe by the World Health Organization. The aim of this paper is to summarize and review of published information focusing on noise annoyance from industrial activities and mining. A search for articles was performed using the bibliographic databases platforms. The epidemiological evidence shows that environmental noise may be associated with cardiovascular and metabolic diseases, impaired cognitive development in children, mental health, post-irritability, and sleep disturbances. As a result of efforts to minimize the effects of industrial noise on human health, the New South Wales Environment Protection Authority published A Guide to the Noise Policy for Industry in 2017, which sets out recommended noise levels, methods, and procedures for noise management based on the latest scientific evidence. Social networks can be used to assess the population's noise annoyance and to verify the effectiveness of the measures. The industrial noise sources are typically defined by low-frequency noise. Low-frequency noise has very low attenuation and is only slightly affected by obstacles, therefore it can be a major cause of night noise annoyance. An association was confirmed between exposure to low-frequency noise and sleep disturbance, psychological problems, cognitive impairment, increased social conflicts, anxiety, emotional instability, nervousness, and reduced mental performance - concentration, and visual perception. In view of the long tradition of mining and industry, the assessment of noise from these activities from the perspective of its impacts on human health is an inherent part of legislative processes. Med Pr Work Health Saf. 2024;75(5):425-431.
Keywords: Environmental Exposure; vystavení vlivu životního prostředí; hluk; Humans; lidé; Noise; Noise, Occupational; hluk na pracovišti